Материалы к фауне комаров-лимониид (Diptera, Limoniidae) СССР. I. Подсемейство Eriopterinae, род Arctoconopa Аl. - Савченко, Е.Н. (Вестник зоологии, 1971)
In the Limoniid-fly fauna of the USSR the following seven species of the genus Arctoconopa A 1. are presented: melampodia-group — A. melampodia (Lw.), A. obscuripes (Ztt.), A. zonata (Ztt.) and A. taimyrensis (Lack.) ; forcipata-group — A. forcipata (Lundstr.) , A. insulana S a v. sp. n. and A. kostjukovi S a v., sp. n. The both new species are closely related and superficially very similar to A. forcipata. They differ only in the structure of male hypopygium, especially in the dorsal gonostyles (Fig. 1 and 2). The South Sakhalin is terra typica of the A. insulana, the Tuva Autonomous SSR —of the A. kostjukovi. The holo- and allotypes of the both new species are preserved in the collection of the Institute of Zoology, Academy of Sciences of the Ukrainian SSR.